2018
DOI: 10.3390/polym10060633
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Rhodamine B Degradation by Ag Nanoclusters-Loaded g-C3N4 Nanosheets

Abstract: In this paper, silver (Ag) nanoclusters-loaded graphitic carbon nitride (g-C 3 N 4 ) nanosheets are synthesized and their physical properties as well as photocatalytic activities are systematically investigated by different techniques. The existence of Ag atoms in the form of nanoclusters (NCs) rather than well-crystallized nanoparticles are evidenced by X-ray diffraction patterns, SEM images, and XPS spectra. The deposition of Ag nanoclusters on the surface of g-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…However, elemental mapping clearly showed the smooth distribution of not only C and N but also Ag on g-C 3 N 4 . This confirmed the presence of element Ag on g-C 3 N 4 . , …”
supporting
confidence: 75%
“…However, elemental mapping clearly showed the smooth distribution of not only C and N but also Ag on g-C 3 N 4 . This confirmed the presence of element Ag on g-C 3 N 4 . , …”
supporting
confidence: 75%
“…Studies based on g-C 3 N 4 have been mostly carried out in attempt to reduce the recombination rate of photogenerated electron-hole pairs, in addition to reduce the energy band gap. Effective procedures may be referred to as—(i) creating heterojunctions like semiconductor-semiconductor [ 29 , 30 , 31 ] or metal-semiconductor [ 32 , 33 , 34 ] in order to effectively separate electrons and holes; (ii) doping metallic elements into g-C 3 N 4 as electron trapping centers [ 35 , 36 ], leaving highly oxidized holes. Recent works showed that the incorporation of metal ions into g-C 3 N 4 polymerization network not only improves charge carrier lifetime and mobilities but also reduces the band gap of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the presence of a small number of dyes in solution is highly visible. The natural deterioration of these dyes in wastewater is very difficult and takes a long time with complicated processes [9,10].…”
Section: Introductionmentioning
confidence: 99%